Study of substrate dependence on the chemoselectivity of the gold-catalysed cycloisomerisation of aryl substituted 1,7-enynes - Huang, Chuhui (2013)
The effects of starting material substitution patterns on reaction selectivity for the gold(I)-catalysed cycloisomerisations of aryl substituted 1,7-enynes were investigated. The results indicated the chemoselectivity of the reaction to be highly substrate and catalyst dependent. Either the piperidine or the tetrahydro-1H-azepine product was obtained in moderate to excellent yields depending on the steric and/or electronic nature of the substrate and the gold(I) catalyst. Overall, six-membered nitrogen ring formation was found to be favoured in reactions with 1,7-enyne derivatives containing a disubstituted alkene moiety or not bearing a sterically bulky substituent or a gold(I) catalyst with a pendant sterically unencumbered phosphine ligand. Formation of the seven-membered nitrogen heterocycle was observed in reactions where the substrate contained a tetrasubstituted alkene unit or a sterically demanding substituent.